Ends of epidemics (2020)
We know a good deal about beginnings: those first signal cases of pneumonia in Guangdong, influenza in Veracruz, and hemorrhagic fever in Guinea, respectively marking the origins of the SARS outbreak of 2002–4, the H1N1 influenza pandemic of 2008–9, and the Ebola pandemic of 2014–16. Recent history tells us a lot about how epidemics unfold, outbreaks spread, and how they are controlled before they spread too far. These stories only get us so far, however, in coming to terms with the global crisis of COVID-19. In the first few months of 2020 the coronavirus pandemic blew past most efforts at containment, snapped the reins of case-detection and surveillance across the world, and saturated all inhabited continents. To understand possible endings for this epidemic, we must look back much further indeed.